2020
DOI: 10.1590/1414-431x20198960
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulated miR-106b inhibits ox-LDL-induced endothelial cell apoptosis in atherosclerosis

Abstract: This research aimed to explore the molecular mechanism of microRNA (miR)-106b in cell apoptosis of atherosclerosis (AS). Human aortic endothelial cells (HAECs) were divided into control group, oxidized-low-density lipoproteins (ox-LDL) group, miR-106b NC+ox-LDL group, miR-106b mimics+ox-LDL group, miR-106b mimics+PTEN+ox-LDL group, and miR-106b mimics +empty+ox-LDL group. Real-time fluorescence quantitative polymerase chain reaction, cholecystokinin, TdT-mediated biotinylated nick end-labeling assay, luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…In the established macrophage related ceRNA subnetwork, the two lncRNA AL138756.1 and LINC01094 lack sufficient investigation, while for the downregulated miRNAs, some of them have been implicated to be protective against AS. miR-106b can inhibit ox-LDL-induced endothelial cell apoptosis in AS [ 20 ]. It also inhibits the expression of PTEN in vascular ECs, which could block TNF-α-induced activation of caspase-3, thus preventing ECs apoptosis in AS [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the established macrophage related ceRNA subnetwork, the two lncRNA AL138756.1 and LINC01094 lack sufficient investigation, while for the downregulated miRNAs, some of them have been implicated to be protective against AS. miR-106b can inhibit ox-LDL-induced endothelial cell apoptosis in AS [ 20 ]. It also inhibits the expression of PTEN in vascular ECs, which could block TNF-α-induced activation of caspase-3, thus preventing ECs apoptosis in AS [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, clinical treatment of AS mainly includes pharmacological therapy and revascularization therapy. Ox-LDL induces the proliferation and migration of smooth muscle cells and is considered to be a key factor in AS development [ 23 ]. Moreover, Ox-LDL is an important pathogenic factor that induces excessive oxidative stress and apoptosis in vascular endothelial cells, which ultimately promoted AS development [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the growth factors and cytokines secreted by infiltrating white cells also affect the proliferation of smooth muscle cells (30). Ox-LDL is a carrier of oxygen-free radicals, which can produce toxic effects on vascular cells, promote their apoptosis and cause vascular endothelial damage (31). In the present study, the results of flow cytometry showed that the apoptotic rate of the ox-LDL group was significantly increased compared with the control group and S/V pretreatment could significantly reduce the apoptotic rate.…”
Section: Discussionmentioning
confidence: 99%